Acute kidney injury in children with moderate-severe COVID-19 and multisystem inflammatory syndrome in children: a referral center experience. - Tastemel Ozturk, Tugba; Düzova, Ali; Oygar, Pembe Derin; Baltu, Demet; Ozcilingir Hakverdi, Pelin; Lacinel Gurlevik, Sibel; Kurt-Sukur, Eda Didem; Aykan, Hayrettin Hakan; Ozen, Seza; Ertugrul, Ilker; Kesici, Selman; Gulhan, Bora; et al. (Pediatric Nephrology, 2024)
Background: Data on the characteristics of acute kidney injury (AKI) in pediatric COVID-19 and MIS-C are limited. We aimed to define the frequency, associated factors and early outcome of AKI in moderate, severe or critical COVID-19 and MIS-C; and to present a tertiary referral center experience from Türkiye. Methods: Hospitalized patients ≤ 18 years of age with confirmed COVID-19 or MIS-C at İhsan Doğramacı Children's Hospital, Hacettepe University, between March 2020—December 2021 were enrolled. The characteristics of AKI in the COVID-19 group were investigated in moderate, severe and critically ill patients; patients with mild COVID-19 were excluded. Results: The median (Q1-Q3) age in the COVID-19 (n = 66) and MIS-C (n = 111) groups was 10.7 years (3.9–15.2) and 8.7 years (4.5–12.7), respectively. The frequency of AKI was 22.7% (15/66) in COVID-19 and 15.3% (17/111) in MIS-C; all MIS-C patients with AKI and 73.3% (11/15) of COVID-19 patients with AKI had AKI at the time of admission. Multivariate analyses revealed need for vasoactive/inotropic agents [Odds ratio (OR) 19.233, p = 0.002] and presence of vomiting and/or diarrhea (OR 4.465, p = 0.036) as independent risk factors of AKI in COVID-19 patients; and need for vasoactive/inotropic agents (OR 22.542, p = 0.020), procalcitonin and ferritin levels as independent risk factors of AKI in the MIS-C group. Age was correlated with lymphocyte count (r = -0.513, p < 0.001) and troponin level (r = 0.518, p < 0.001) in MIS-C patients. Length of hospital stay was significantly longer in both groups with AKI, compared to those without AKI. Mortality was 9.1% in the COVID-19 group; and was associated with AKI (p = 0.021). There was no mortality in MIS-C patients. AKI recovery at discharge was 63.6% in COVID-19 survivors and 100% in MIS-C patients. Conclusions: Independent risk factors for AKI were need for vasoactive/inotropic agents and vomiting/diarrhea in moderate, severe or critical COVID-19 patients; and need for vasoactive/inotropic agents and severe inflammation in MIS-C patients. Our findings suggest that inflammation and cardiac dysfunction are associated with AKI in MIS-C patients; and the association with age in this group merits further studies in larger groups. Early outcome is favorable; long-term follow-up for kidney functions is needed.